2021
DOI: 10.1097/as9.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment and Outcomes of Colorectal Cancer Patients During the COVID-19 Pandemic: A National Population-based Study in England

Abstract: Objective: To compare the management and outcomes of colorectal cancer (CRC) patients during the first 2 months of the COVID-19 pandemic with the preceding 6 months. Background: The pandemic has affected the diagnosis and treatment of CRC patients worldwide. Little is known about the safety of major resection and whether creating “cold” sites (COVID-free hospitals) is effective. Methods: A national study in England used administrative hospital da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…After screening 283 abstracts generated by the search algorithm, 10 studies were deemed eligible for inclusion in the final quantitative analysis ( Figure 1 ). In total, 26,808 patients were incorporated in the analysis (19,152 in the pre-pandemic cohort and 7656 in the pandemic cohort), with five studies being from east Asia (one from Japan [ 14 ], two from China [ 15 , 16 ], and two from Korea [ 17 , 18 ]) and the remaining five from Europe (two from the United Kingdom [ 11 , 19 ], one from Italy [ 20 ], one from Ireland [ 3 ], and one from Serbia [ 21 ]). The size of the pandemic cohorts in each study was compared to that of the pre-pandemic cohorts after matching for the time duration of the data collection in the pandemic cohorts (in months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening 283 abstracts generated by the search algorithm, 10 studies were deemed eligible for inclusion in the final quantitative analysis ( Figure 1 ). In total, 26,808 patients were incorporated in the analysis (19,152 in the pre-pandemic cohort and 7656 in the pandemic cohort), with five studies being from east Asia (one from Japan [ 14 ], two from China [ 15 , 16 ], and two from Korea [ 17 , 18 ]) and the remaining five from Europe (two from the United Kingdom [ 11 , 19 ], one from Italy [ 20 ], one from Ireland [ 3 ], and one from Serbia [ 21 ]). The size of the pandemic cohorts in each study was compared to that of the pre-pandemic cohorts after matching for the time duration of the data collection in the pandemic cohorts (in months).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Kuryba et al [ 19 ] was the only study to report data on mortality, derived from a large UK-based population registry, revealing 2.6% mortality rates in the pandemic cohort versus 1.6% in the pre-pandemic one. The encountered marginal increase in mortality was mainly attributable to emergency surgery cases (OR 1.74, p = 0.003) and was especially pronounced in so-called “hot-sites”, i.e., centers that accommodated COVID-19 positive patients as well as elective and emergency colorectal cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians must treat cancer patients in accordance with their individual characteristics, the involved organ(s), the tumor stage, and the available adjuvant treatments. Although some studies have indicated an increase in T4 stage cancer during the pandemic, most have reported no significant upstaging in terms of the TNM classification ( Table 3 ) [ 8 28 33 57 58 59 60 61 62 63 ]. A hasty or obstinate selection of surgical resection is thus unnecessary in positive COVID-19 cases if other treatment modalities are available.…”
Section: Resultsmentioning
confidence: 99%
“…In the early stages of the pandemic, concerns regarding the risk of SARS-CoV-2 exposure, susceptibility to infection, and severity of COVID-19 for people with cancer led to cancer treatment changes in different countries and settings [33] , [34] , [35] , [36] , [37] , [38] , [39] . The precautionary principle is important in early and urgent decision-making; however, treatment changes can also have negative effects, so it is crucial to generate high-quality timely evidence on the magnitude of risks to inform more nuanced decisions.…”
Section: Discussionmentioning
confidence: 99%